Pepper SBP-box transcription factor, CaSBP13, plays a negatively role in drought response - Zhang, Huai-Xia; Zhang, Yuan; Zhang, Bo-Wen (Frontiers in Plant Science, 2024)
The SBP-box gene significantly influences plant growth, development, and stress responses, yet its function in pepper plants during drought stress remains unexplored. Using virus-induced gene silencing and overexpression strategies, we examined the role of CaSBP13 during drought stress in plants. The results revealed that the expression of CaSBP13 can be induced by drought stress. Silencing of CaSBP13 in pepper notably boosted drought resistance, as evident by decreased active oxygen levels. Furthermore, the water loss rate, relative electrical conductivity, malondialdehyde content, and stomatal density were reduced in CaSBP13-silenced plants compared to controls. In contrast, CaSBP13 overexpression in Nicotiana benthamiana decreased drought tolerance with elevated reactive oxygen levels and stomatal density. Additionally, ABA signaling pathway genes (CaPP2C, CaAREB) exhibited reduced expression levels in CaSBP13-silenced plants post drought stress, as compared to control plants. On the contrary, CaPYL9 and CaSNRK2.4 showed heightened expression in CaSBP13-sienced plants under the same conditions. However, a converse trend for NbAREB, NbSNRK2.4, and NbPYL9 was observed post-four day drought in CaSBP13-overexpression plants. These findings suggest that CaSBP13 negatively regulates drought tolerance in pepper, potentially via ROS and ABA signaling pathways.